Lewis Acid Catalyzed Regio- and Diastereoselective Synthesis of Spiroisoxazolines via One-Pot Sequential Knoevenagel Condensation/1,3-Dipolar Cycloaddition Reaction - Yazdani, Hossein; Bazgir, Ayoob (Synthesis, 2019)
A ZnCl2-catalyzed regio- and diastereoselective one-pot sequential Knoevenagel condensation/1,3-dipolar cycloaddition reaction of CH acids (oxindole, 1,3-indandione, and 3H-pyrazol-3-one), aldehydes, and dibromoformaldoxime has been established. The method allows the synthesis of diversely functionalized spiroisoxazolines in good isolated yields under mild reaction conditions. Moreover, the preparation of spiroindene-isoxazole-1,3-diones containing benzoimidazole or benzothiazole moieties as new ligands for the metal-catalyzed coupling reactions and C–H activation is demonstrated.
Keywords: 1,3-dipolar cycloaddition reaction; isoxazolines; nitrile oxides; spirooxindoles; spiroindandiones; coupling reaction